AN ANALYSIS OF INTERPERSONAL MEANING ON TEACHERâS SCAFFOLDING TALKS - Rahma, Yeny (ENCOUNTER, 2012)
Learning and teaching a language is not simply a matter of learning and teaching vocabulary and grammar, but we have to understand the context of culture and other peopleâs meanings because we share the same cultural knowledge. When we have a communication orally or in writing, we make selections to choose appropriate meanings for the field, tenor and mode of a context of situation (David Butt et al, 1995:23).As tenor is also significant in the context of situation, it is also needed to be analyzed as it is closely related to interpersonal metafunction or meaning. When people communicate, they actually exchange commodity. The commodity itself is divided into two parts namely information and goods and services. When they demand or give information, they create either question or statement. If they demand or give goods or services, they will create either command or offer (Suzanne Eggins, 1994:146-153).The analysis of interpersonal meaning deals with two components that are mood element and residue element of the clause. The mood element includes subject, finite and/or mood adjunct while the residue consists of predicator, complement and some adjuncts such as mood, polarity, comment, vocative or circumstancial adjunct (Suzanne Eggins, 1994:154-169).